The Da’wah Strategy of Al-Jam’iyatul Washliyah in Enhancing Social Awareness of The Community - Aritonang, Idris; Abdullah, Abdullah (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
Dakwah in the midst of the social dynamics of modern society faces challenges in the form of declining social awareness, weakening solidarity, and low community participation in social life. These conditions require a dakwah strategy that is not only normative in nature, but also capable of encouraging social transformation. This study aims to analyze Al-Jam'iyatul Washliyah's da'wah strategy in raising social awareness among the people of North Labuhanbatu Regency. The study uses a qualitative method with a descriptive approach. Primary data was obtained through in-depth interviews with Al-Jam'iyatul Washliyah administrators and local da'i, while secondary data was sourced from scientific journals and relevant documents. The results show that Al-Jam'iyatul Washliyah implements an integrative da'wah strategy through dakwah bil-lisan, bil-qalam, and bil-hal, which are structured contextually and involve religious leaders, the community, and local government. The implementation of dakwah bil-hal through social activities and humanitarian actions has proven effective in fostering empathy, solidarity, and social awareness among the community. These findings imply the importance of strengthening Islamic organization-based social da'wah as a model for sustainable social awareness development.